Novel technique for reconstruction of challenging defects around knee joint: distally based split vastus lateralis myocutaneous flap and review of literature - Agarkhedkar, Nikhil; Wahegaonkar, Chandrashekhar; Patil, Bhushan; Dogra, Bharat Bhushan (International Journal of Research in Medical Sciences, 2017)
Background: Reconstruction of soft tissue defects around the knee joint is often challenging because of exposed bone or tendon, infected wound, open joint or exposed implant or prosthesis. The aim of the study was to analyse feasibility of distally based split vastus lateralis myocutaneous (VL-MC) flap for covering soft tissue defects around knee joint and To report a new technique for coverage of soft tissue defects around knee joint with distally based split Vastus Lateralis myocutaneous (VL-MC) flap and to assess functional and aesthetic outcome. Methods: A total of 3 distally based split Vastus Lateralis myocutaneous flaps were used for reconstruction of soft tissue defects and exposed implant around knee and upper third of tibia. Defect sizes ranged from 5x7 cm to 12x10 cm size. A systematic review of Literature was done using key words of distally based split vastus lateralis myocutaneous flap and various articles were reviewed. The patients were followed up in postoperative period for assessment of this flap considering functional and aesthetic parameters. Results: The flap survived well without any loss in all 3 cases. The donor site was closed primarily in all the cases. Complete functional recovery was achieved by 4 weeks. Patients were satisfied with aesthetic appearance as well. Conclusion: Distally based split VL-MC flap is a safe and reliable option for reconstruction of the complex defects around knee.